Wnt signaling regulates smooth muscle precursor development in the mouse lung via a tenascin C/PDGFR pathway - Cohen, Ethan David; Ihida-Stansbury, Kaori; Lu, Min Min; Panettieri, Reynold A.; Jones, Peter Lloyd; Morrisey, Edward E. (The Journal of Clinical Investigation, 2009)
Paracrine signaling from lung epithelium to the surrounding mesenchyme is important for lung SMC development and function and is a contributing factor in an array of pulmonary diseases such as bronchopulmonary dysplasia, pulmonary hypertension, and asthma. Wnt7b, which is exclusively expressed in the lung epithelium, is important for lung vascular smooth muscle integrity, but the underlying mechanism by which Wnt signaling regulates lung SMC development is unclear. In this report, we have demonstrated that Wnt7b regulates a program of mesenchymal differentiation in the mouse lung that is essential for SMC development. Genetic loss-of-function studies showed that Wnt7b and β-catenin were required for expression of Pdgfrα and Pdgfrβ and proliferation in pulmonary SMC precursors. In contrast, gain-of-function studies showed that activation of Wnt signaling increased the expression of both Pdgfrα and Pdgfrβ as well as the proliferation of SMC precursors. We further showed that the effect on Pdgfr expression was, in part, mediated by direct transcriptional regulation of the ECM protein tenascin C (Tnc), which was necessary and sufficient for Pdgfrα/β expression in lung explants. Moreover, this pathway was highly upregulated in a mouse model of asthma and in lung tissue from patients with pulmonary hypertension. Together, these data define a Wnt/Tnc/Pdgfr signaling axis that is critical for smooth muscle development and disease progression in the lung.